Economic implications of the loss of glyphosate and paraquat on Australian mixed enterprise farms. (October 2021) - Walsh, Alison; Kingwell, Ross
Abstract: CONTEXT: Glyphosate and paraquat are effective, affordable non-selective herbicides widely used in Australian agriculture. However, for reasons described in this study, their use is under threat and a ban on their use is a possibility. OBJECTIVE: This study describes the farm business and farming system changes resulting from a ban on use of glyphosate and paraquat in a main mixed farming region of Australia. METHODS: The bioeconomic farm model, MIDAS, is used to represent mixed enterprise farms of Western Australia. The model incorporates the suite of management strategies and tactics farmers are likely to employ in response to loss of access to the key herbicides, glyphosate and paraquat. Scenario analyses are applied to different farm types. RESULTS AND CONCLUSIONS: Loss of these herbicides is estimated to cause increased costs of crop production and large declines in farm profit, if the herbicide ban does not similarly apply to other major grain exporters. Farming systems shift towards sheep production and away from cropping, increasing farm greenhouse gas emissions. Farm businesses that are more crop dominant experience the greatest declines in profit. However, if a global ban on glyphosate and paraquat applies, then Australian farm businesses will be advantaged as they rely far less on glyphosate-tolerant crops. SIGNIFICANCE: Despite several tactics and investments that farmers might employ to combat the loss of these herbicides, none prevents a reduction in farm profit. For all farm types considered under all management scenarios, loss of these herbicides generates sizeable declines farm profit. The likelihood of such large declines in profit however should spur the invention and development of cost-effective means of weed control. Graphical abstract: Unlabelled Image Highlights: A ban on glyphosate and paraquat solely in Australia will increase cropping costs and cause large declines in farm profit. Farming systems will shift towards sheep production and away from cropping, increasing farms' greenhouse gas emissions. Farm businesses that are more crop dominant will experience the greatest declines in profit. Tactics and investments farmers might employ to combat loss of these herbicides will not prevent reduced farm profit. A global ban on these herbicides will increase grain prices. Australian farmers will benefit as they rely less on GT crops.